How to write and publish a scientific paper - Gastel, Barbara; Day, Robert A. 1924-2021 (Santa Barbara, California Greenwood, 2022)
"Thoroughly updated throughout, this classic, practical text on how to write and publish a scientific paper takes its own advice to be "as clear and simple as possible"--
Includes bibliographical references (pages 321-329) and index.
Keywords: Technical writing; LANGUAGE ARTS & DISCIPLINES / Publishers & Publishing Industry; SCIENCE / Research & Methodology